2019
DOI: 10.1002/cne.24757
|View full text |Cite
|
Sign up to set email alerts
|

Intratelencephalic projections of the avian visual dorsal ventricular ridge: Laminarly segregated, reciprocally and topographically organized

Abstract: Recent reports have shown that the avian visual dorsal ventricular ridge (DVR) is organized as a trilayered complex, in which the forming layers—the thalamo‐recipient entopallium (E), an overlaying nidopallial stripe called intermediate nidopallium (NI), and the dorsally adjacent mesopallium ventrale—appear to be extensively interconnected by topographically organized columns of reciprocal axonal processes running perpendicular to the layers, an arrangement highly reminiscent to that of the sensory cortices of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 108 publications
8
33
0
Order By: Relevance
“…Finally, it is worth noting that in the sagittal plane used in this study all major sensory areas of the DVR, as well as its forming sensory layer‐like partitions (as described previously by Ahumada‐Galleguillos et al, 2015; Fernández, Ahumada‐Galleguillos, et al, 2020; Jarvis et al, 2013), can be appreciated in a rostro‐caudal continuity in EAG2 in situ hybridization preparations. In this preparation, each and all of the senso‐recipient layers of the DVR display substantial numbers of EAG2 positive somata (Figure 3).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Finally, it is worth noting that in the sagittal plane used in this study all major sensory areas of the DVR, as well as its forming sensory layer‐like partitions (as described previously by Ahumada‐Galleguillos et al, 2015; Fernández, Ahumada‐Galleguillos, et al, 2020; Jarvis et al, 2013), can be appreciated in a rostro‐caudal continuity in EAG2 in situ hybridization preparations. In this preparation, each and all of the senso‐recipient layers of the DVR display substantial numbers of EAG2 positive somata (Figure 3).…”
Section: Resultssupporting
confidence: 55%
“…A prominent feature of the amniote pallial telencephalon is the presence of specialized areas receiving ascending projections from different sensory modalities (Buttler & Hodos, 2005). In mammals, these ascending sensory pathways innervate distinct regions of the dorsolateral pallium, which is elaborated as a six-layered cortex in these vertebrates (Fernandez et al, 1998;Puelles, 2001;Puelles et al, 2000;Striedter, 1997). In birds, most of these sensory pathways innervate different areas of the ventro-lateral pallium, which is formed by a set of prominent nuclear-like divisions protruding into the ventricle, together termed dorsal ventricular ridge (DVR; Dubbeldam, 1998;Karten, 1969).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works suggested that the NI (considered as Ep and Ep2) projection to the lateral pallium was segregated in the anterior–posterior axis, such that the anterior NI projected to the NFL, the central NI to the NIL, and the posterior NI to the NCL (Husband & Shimizu, ). However, Fernández et al () have shown that the entire NI projects to each of its targets including the mentioned nidopallial areas and the Arc, and therefore, a complete representation of the Rt subdivisions should be expected in all structures. Nonetheless, in accordance with Husband and Shimizu (), Fernández et al () also found that the RtDa‐related zone in the anterior NI projects more densely to the NFL than to the NCL.…”
Section: Discussionmentioning
confidence: 99%
“…However, Fernández et al () have shown that the entire NI projects to each of its targets including the mentioned nidopallial areas and the Arc, and therefore, a complete representation of the Rt subdivisions should be expected in all structures. Nonetheless, in accordance with Husband and Shimizu (), Fernández et al () also found that the RtDa‐related zone in the anterior NI projects more densely to the NFL than to the NCL. In addition, the RtCe projection seems to be heavily oriented to the striatum, which may thus leave a weak representation of this division in the NI.…”
Section: Discussionmentioning
confidence: 99%